Method for manufacturing a gasoline particulate filter - Patents.com

By coating detergent paste containing platinum group metals, oxygen storage capacity (OSC) materials and aliphatic analytes on gasoline particulate filters (GPFs) and baking them to form GPFs, the problem of insufficient catalytic activity and backpressure pressure of existing GPFs is solved, and more efficient catalytic performance and lower backpressure pressure are achieved.

JP2025513795AActive Publication Date: 2025-04-30JOHNSON MATTHEY PLC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024559342
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-05-27
Filing Date
2023-05-23
Publication Date
2025-04-30
Estimated Expiration
2043-05-23

AI Technical Summary

Technical Problem

Existing gasoline particulate filters (GPFs) have shortcomings in catalytic activity and backpressure pressure, especially after combining with the three-way catalyst coating, the backpressure pressure increases and the conversion performance of CO, NOx and HC is poor.

Method used

A method of making gasoline particulate filters (GPFs) is employed, which includes forming a detergent paste, coating a fluid wall filtering substrate to form a detergent paste covered substrate, and then baking to form gasoline particulate filters (GPFs). Detergent pastes include platinum group metals, oxygen storage capacity (OSC) materials and C2 to C6 containing aliphatic acine.

Benefits of technology

GPFs produced by this method have significantly improved in terms of catalytic activity and backpressure pressure, enabling more efficient conversion of CO, NOx and HC while reducing backpressure pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025513795000002
    Figure 2025513795000002
  • Figure 2025513795000003
    Figure 2025513795000003
  • Figure 2025513795000004
    Figure 2025513795000004
Patent Text Reader

Abstract

A method for the manufacture of a gasoline particulate filter (GPF) for the treatment of exhaust gases is disclosed. The method includes (i) forming a washcoat slurry, (ii) coating a wall-flow filter substrate with the washcoat slurry to form a washcoated substrate, and (iii) calcining the washcoated substrate to form a gasoline particulate filter. The washcoat slurry includes (a) a platinum group metal selected from the group consisting of Pt, Pd, Rh, and mixtures thereof, (b) an oxygen storage capacity (OSC) material, and (c) a C2-C6 aliphatic amino acid.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for providing a catalyzed wall-flow filter suitable for use in emission treatment systems, particularly emission treatment systems for positive ignition internal combustion engines, such as gasoline spark ignition engines. The present invention provides a method for manufacturing a gasoline particulate filter having improved catalytic activity and reduced backpressure. [Background technology]

[0002] The gasoline particulate filter (GPF) is an emissions aftertreatment technology based on the diesel particulate filter (DPF) that was developed to control particulate emissions from gasoline direct injection (GDI) engines.

[0003] Most early GPF applications involved an uncoated GPF positioned downstream of a three-way catalyst (TWC). As the technology matured, GPFs have also been coated with a three-way catalyst. This catalyst-coated GPF configuration is sometimes referred to as a four-way catalyst. However, the combination of a catalyst coating on the filter body introduces additional issues such as excessive backpressure and the need for minimal CO, NO, or other impurities. x , and there are requirements for HC conversion properties.

[0004] WO2017056067A1 discloses a catalytic wall-flow monolith filter having three-way catalytic activity for use in the emission treatment system of a positive ignition internal combustion engine, characterized by having an amount by weight of platinum group metal per unit volume of the on-wall coating present on the channel wall surface that varies continuously along the length or by varying wall thickness.

[0005] WO 2020201953(A1) discloses a catalytic article for treating exhaust gas emissions from gasoline engines, in particular a wall-flow filter suitable for treating particulate emissions having a size of less than 23 nm, which is achieved by the use of a specific particulate oxygen storage component having a controlled particle size.

[0006] US Patent No. 10570063(B1) discloses the use of beta-alanine as a dispersant in the production of nanosuspension mixed oxides. There is no suggestion in US Patent No. 10570063(B1) that these may be desirably used in exhaust gas treatment applications.

[0007] WO2017178801A1 discloses a method of coating a substrate with a foam, the method comprising: (a) introducing foam into a substrate comprising a plurality of channels through open ends of the channels at a first end of the substrate, and (b) optionally applying (i) a vacuum to the open ends of the channels at a second end of the substrate and / or (ii) a pressure to the open ends of the channels at the first end of the substrate, the foam comprising a particulate material, the foam being particle stabilized.

[0008] An object of the present invention is to provide an improved method for producing GPFs to address problems associated with the prior art. Summary of the Invention

[0009] The present invention relates to a method for the manufacture of a gasoline particulate filter (GPF) for the treatment of exhaust gases, the method comprising the steps of: (i) forming a washcoat slurry; (ii) coating a wall-flow filter substrate with the washcoat slurry to form a washcoated substrate; (iii) calcining the washcoated substrate to form a GPF; The washcoat slurry comprises: (a) a platinum group metal selected from the group consisting of Pt, Pd, Rh, and mixtures thereof; (b) an oxygen storage capacity (OSC) material; and (c) C 2 ~C 6 and aliphatic amino acids. [Brief description of the drawings]

[0010] [Figure 1] SEM images of the anterior central portion of GPF-A (top) and GPF-B (bottom) are shown. [Diagram 2] Figure 1 shows cumulative NOx during a JLR RDE drive cycle for hydrothermally aged GPF-A compared to that of hydrothermally aged GPF-C. The solid line correlates to GPF-A. The dashed line correlates to GPF-C. The grey line correlates to vehicle speed. [Diagram 3] T50 light-off temperatures for CO, THC (total hydrocarbons), and NOx are shown. Solid bars correlate to GPF-A. Dashed bars correlate to GPF-C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present disclosure will now be further described. In the following sections, different aspects / embodiments of the present disclosure are defined in more detail. Each aspect / embodiment so defined may be combined with any other aspect / embodiment or aspect / embodiment, unless expressly indicated otherwise. In particular, any feature indicated as being preferred or advantageous may be combined with any other feature or features indicated as being preferred or advantageous.

[0012] The present invention relates to a method for the manufacture of a gasoline particulate filter (GPF) for the treatment of exhaust gases, the method comprising the steps of: (i) forming a washcoat slurry; (ii) coating a wall-flow filter substrate with the washcoat slurry to form a washcoated substrate; (iii) firing the washcoated substrate to form a gasoline particulate filter; The washcoat slurry comprises: (a) a platinum group metal selected from the group consisting of Pt, Pd, Rh, and mixtures thereof; (b) an oxygen storage capacity (OSC) material; and (c) C 2 ~C 6 and aliphatic amino acids.

[0013] Thus, within the scope of the present invention, a gasoline particulate filter refers to a catalyst coated wall-flow filter substrate.

[0014] A wall-flow filter substrate typically has a first face and a second face defining a longitudinal direction therebetween, and first and second pluralities of channels extending longitudinally, the first plurality of channels being open at the first face and closed at the second face, the channels of the first plurality of channels being defined in part by channel walls, the second plurality of channels being open at the second face and closed at the first face, the channels of the second plurality of channels being defined in part by channel walls, and the channel walls between the channel walls of the first plurality of channels and the channel walls of the second plurality of channels being porous.

[0015] The wall-flow filter substrate can be a ceramic porous substrate such as cordierite, aluminum titanate, silicon carbide, and the like. The filter substrate can have a porosity of 40-75%, such as 45-70% or 50-60%.

[0016] The method includes forming a washcoat slurry. The washcoat slurry includes a solvent. Water is a preferred solvent for the washcoat slurry.

[0017] The washcoat slurry comprises platinum group metals (PGMs) selected from the group consisting of Pt, Pd, Rh, and mixtures thereof. Preferably, the washcoat slurry comprises Pt and Rh, or Pd and Rh. For example, the washcoat slurry may comprise Pt and Rh. Alternatively, the washcoat slurry may comprise Pd and Rh. The amount of total PGMs in the washcoat slurry may be 0.005-10 wt%, preferably 0.001-5 wt%, more preferably 0.05-3.0 wt%, based on the total weight of the washcoat slurry.

[0018] The washcoat slurry includes an oxygen storage capacity (OSC) material. "Oxygen storage capacity" refers to the ability of a material used as an oxygen storage capacity material in a catalyst to store oxygen under lean conditions and release oxygen under rich conditions.

[0019] The OSC material may be ceria or a mixed oxide comprising ceria. Preferably, the OSC material comprises a mixed oxide of cerium and zirconium; a mixed oxide of cerium, zirconium, and aluminum; a mixed oxide of cerium, zirconium, and neodymium; or a mixed oxide of cerium, zirconium, and praseodymium. The term "mixed oxide" as used herein generally refers to a mixture of oxides in a single phase, as conventionally known in the art. In one embodiment, the OSC material comprises a cerium-zirconium mixed oxide nanosol having an average particle size of less than 1 μm. In another embodiment, the OSC material comprises a cerium-zirconium mixed oxide having an average particle size of 1-20 μm, preferably 2-15 μm, more preferably 5-10 μm.

[0020] The amount of OSC material in the washcoat slurry can be from 5 to 50 wt %, preferably from 10 to 30 wt %, based on the total weight of the washcoat slurry.

[0021] The wash coat slurry is C 2 ~C 6Contains aliphatic amino acids. 2 ~C 6 Aliphatic amino acids include 3-amino-propionic acid, L-alanine, glycine, serine, L-valine, and the like. 2 ~C 6 Aliphatic amino acids have the formula HO 2 C-(CH 2 ) n -NH 2 where n is 1 to 5, preferably 1 to 3. One preferred amino acid is 3-amino-propionic acid (n=2).

[0022] C in washcoat slurry 2 ~C 6 The amount of the aliphatic amino acid may be 1-50% by weight, preferably 2-40% by weight, more preferably 5-30% by weight based on the crucible solid in the washcoat slurry.

[0023] The washcoat slurry may further comprise an inorganic oxide support. The inorganic oxide support may be an oxide of an element of Groups 2, 3, 4, 5, 13, and 14. The inorganic oxide support is preferably a refractory oxide that exhibits chemical and physical stability at high temperatures, such as temperatures associated with the exhaust of a gasoline engine. The inorganic oxide support may be selected from the group consisting of alumina, silica, titania, and mixed or composite oxides thereof. More preferably, the inorganic oxide support is alumina. In one embodiment, the inorganic oxide support is gamma-alumina. The gamma-alumina used as the inorganic oxide support preferably has an average particle size of 1 to 10 μm, more preferably 2 to 8 μm. In another embodiment, the inorganic oxide support is nano-alumina. The nano-alumina used as the inorganic oxide support preferably has an average particle size of less than 1 μm.

[0024] The inorganic oxide support may be doped with a dopant. The dopant may be selected from the group consisting of La, Sr, Si, Ba, Y, Pr, Nd, Ce, and mixtures thereof. Preferably, the dopant is La, Ba, or Ce. Most preferably, the dopant is La. The dopant content in the inorganic oxide support may be 1-30% by weight, preferably 2-25% by weight, more preferably 3-20% by weight.

[0025] The amount of the inorganic oxide support in the washcoat slurry can be 2 to 30% by weight, preferably 5 to 20% by weight, based on the total weight of the washcoat slurry.

[0026] The washcoat slurry typically has a solids content of 15 to 40% by weight, more preferably 20 to 35% by weight.

[0027] The method includes coating a wall-flow filter substrate with a washcoat slurry to form a washcoated substrate. Coating may be done by spraying and / or dipping the wall-flow filter substrate. Preferably, the coating is applied to at least one of the inlet and outlet channels of the wall-flow filter substrate. More preferably, the coating is applied to both the inlet and outlet channels. One suitable coating procedure is described in GB Patent No. 2524662(A).

[0028] The method further includes calcining the washcoated substrate to form a GPF. Calcination may be preceded by a drying step at a lower temperature (such as 80-200° C.). Calcination is routine in the art and may be carried out under conventional conditions.

[0029] After calcination, the PGM loading in the GPF is generally around 1 g / ft 3 ~50g / ft 3 , more preferably 5 g / ft 3 ~40g / ft 3The washcoat loading of the calcined GPF is typically 0.2 g / in 3 ~5g / in 3 , more preferably 0.5 g / in 3 ~3g / in 3 It is.

[0030] The present inventors have 2 ~C 6 It has been found that the inclusion of an aliphatic amino acid reduces the viscosity of the washcoat slurry. As a result, the washcoat slurry is able to penetrate deeper into the pores of the substrate, which has been found to reduce backpressure. 2 ~C 6 The inclusion of aliphatic amino acids improves the catalytic performance of GPFs. EXAMPLES

[0031] Example 1 GPF preparation Wash Coat Slurry A-1 Washcoat slurry A-1 was prepared containing Pd nitrate, Rh nitrate, cerium-zirconium mixed oxide nanosol (average particle size 390 nm), gamma phase alumina (average particle size 5 μm), and water. The slurry had a solids content of 25% and a viscosity of >500 cP as measured at 20° C. with a Brookfield™ RV DVII+Extra Pro viscometer using an SC4-27 spindle at a spindle speed of 50 rpm.

[0032] GPF-A (Comparative Example) The washcoat slurry A-1 prepared above was coated from both the inlet and outlet faces of a cordierite wall-flow honeycomb filter substrate (300 cells per square inch, average pore size 17 μm, porosity 66%) using the coating procedure described in GB Patent No. 2524662. A predetermined amount of the slurry was deposited on the top end of the filter substrate using a slurry dosing head. The dosing head has a plurality of openings arranged to dispense the slurry onto the top face of the filter substrate. An open-ended channel at the top end of the filter substrate was coated with a predetermined amount of the slurry by applying a vacuum to the bottom end of the filter substrate to draw the slurry along the channel. The coating length on the inlet channel is about 30% of the substrate length. The coating length on the outlet channel is about 70% of the substrate length. The coated substrate was dried at 110° C. and calcined at 500° C. to produce a GPF. The GPF thereby produced had a coating density of 1.64 g / in 3 Washcoat loading, 35g / ft 3 Pd loading of 10 g / ft 3 The Rh loading is

[0033] The SEM image of the front center section of GPF-A shows that a significant amount of washcoat is present on the wall, as shown in Figure 1(a).

[0034] Wash coat slurry B-1 Washcoat slurry B-1 was prepared containing Pd nitrate, Rh nitrate, mixed ceria-zirconia mixed oxide (average particle size 7 μm), nano alumina boehmite (average particle size 70-120 nm), and water. The washcoat slurry had a solids content of 30%. The slurry had a viscosity of >3000 cP as measured at 20° C. with a Brookfield™ RV DVII+Extra Pro viscometer using an SC4-27 spindle at a spindle speed of 50 rpm.

[0035] Wash coat slurry B-2 Washcoat slurry B-2 was prepared containing Pd nitrate, Rh nitrate, mixed ceria-zirconia based mixed oxide composite (average particle size 7 μm), nano-alumina boehmite (average particle size 70-120 nm), 3-aminopropanoic acid, and water. The amount of 3-aminopropanoic acid is 40 wt% based on the crucible solids in the washcoat slurry. Washcoat slurry B-2 has a solids content of 30%. The slurry had a viscosity of <50 cP as measured at 20° C. with a Brookfield™ RV DVII+Extra Pro viscometer using an SC4-27 spindle at a spindle speed of 50 rpm. The inclusion of 3-aminopropanoic acid significantly reduced the viscosity of the slurry.

[0036] GPF-B GPF-B was prepared following the same procedure as for the preparation of GPF-A, except that washcoat slurry B-2 was used. The resulting GPF-B had a viscosity of 1.64 g / in 3 Washcoat loading, 35g / ft 3 Pd loading of 10 g / ft 3 The Rh loading is

[0037] The SEM image of the anterior central section of GPF-B showed that the washcoat was mainly intramural, as shown in Figure 1(b).

[0038] GPF-C GPF-C was prepared in a similar manner to GPF B, except that the amount of 3-aminopropanoic acid was 6 wt.% relative to the crucible solids in the washcoat slurry. The washcoat slurry had a viscosity of <100 cP as measured at 20° C. with a Brookfield™ RV DVII+Extra Pro viscometer using an SC4-27 spindle at a spindle speed of 50 rpm. The resulting GPF-C had a viscosity of 1.64 g / in 3 Washcoat loading, 35g / ft 3 Pd loading of 10 g / ft 3 The Rh loading was .

[0039] Example 2 Cold Flow Back Pressure Test The cold flow back pressure (BP) of fresh GPF-C and fresh GPF-A (comparative example) is shown in Table 1. The data shows that when the amount of 3-aminopropanoic acid used is 6 wt% of the crucible solids in the washcoat slurry, the cold flow back pressure is reduced.

[0040] [Table 1]

[0041] Example 3. Performance test GPF-C and GPF-A were hydrothermally aged under lean conditions. They were then evaluated on the engine for 3-way performance via a JLR RDE drive cycle evaluation. As shown in Figure 2, a 53% reduction in total NOx over GPF-C was measured compared to a 34% reduction in total NOx over GPF-A. Additionally, as shown in Figure 3, GPF-C provided a 40-50°C light-off benefit in NOx, CO, and THC T50 when compared to GPF-A.

Claims

1. 1. A method for the manufacture of a gasoline particulate filter (GPF) for the treatment of exhaust gases, said method comprising the steps of: (i) forming a washcoat slurry; (ii) coating a wall-flow filter substrate with the washcoat slurry to form a washcoated substrate; (iii) calcining the washcoated substrate to form a gasoline particulate filter; The washcoat slurry comprises: (a) a platinum group metal selected from the group consisting of Pt, Pd, Rh, and mixtures thereof; (b) an oxygen storage capacity (OSC) material; and (c) C 2 ~C 6 and an aliphatic amino acid.

2. Said C 2 ~C 6 The aliphatic amino acid is represented by the formula HO 2 C-(CH 2 ) n -NH 2 2. The method of claim 1, having the formula:

3. The method of claim 2, wherein n is 1 to 3.

4. The method of claim 2 , wherein n is 2.

5. The C in the washcoat slurry 2 ~C 6 2. The method of claim 1, wherein the amount of aliphatic amino acid is 1-50% by weight based on crucible solids in the washcoat slurry.

6. The C in the washcoat slurry 2 ~C 6 2. The method of claim 1, wherein the amount of aliphatic amino acid is from 2 to 40% by weight based on crucible solids in the washcoat slurry.

7. The C in the washcoat slurry 2 ~C 6 2. The method of claim 1, wherein the amount of aliphatic amino acid is 5 to 30 weight percent based on crucible solids in the washcoat slurry.

8. The C in the washcoat slurry 2 ~C 6 The method of claim 4, wherein the amount of aliphatic amino acid is 1-50% by weight based on crucible solids in the washcoat slurry.

9. The C in the washcoat slurry 2 ~C 6 The method of claim 4, wherein the amount of aliphatic amino acid is from 2 to 40% by weight based on crucible solids in the washcoat slurry.

10. The C in the washcoat slurry 2 ~C 6 5. The method of claim 4, wherein the amount of aliphatic amino acid is 5 to 30 weight percent based on crucible solids in the washcoat slurry.

11. The method of claim 1 , wherein the washcoat slurry comprises Pt and Rh.

12. The method of claim 1 , wherein the washcoat slurry comprises Pd and Rh.

13. 10. The method of claim 1, wherein the OSC material comprises a mixed oxide of cerium and zirconium; a mixed oxide of cerium, zirconium, and aluminum; a mixed oxide of cerium, zirconium, and neodymium; or a mixed oxide of cerium, zirconium, and praseodymium.

14. 2. The method of claim 1, wherein the OSC material comprises a cerium-zirconium mixed oxide nanosol having an average particle size of less than 1 μm.

15. The method of claim 1 , wherein the washcoat slurry further comprises an inorganic oxide support.

16. The method of claim 15, wherein the inorganic oxide support comprises alumina.

17. The method of claim 15, wherein the inorganic oxide support comprises gamma-alumina.

18. The C in the washcoat slurry 2 ~C 6 the amount of aliphatic amino acid is 5-30 wt. % based on crucible solids in said washcoat slurry; the OSC material comprises a cerium-zirconium mixed oxide nanosol having an average particle size of less than 1 μm; The method of claim 4, wherein the inorganic oxide support is gamma-alumina having an average particle size of 1 to 10 μm.

19. The C in the washcoat slurry 2 ~C 6 the amount of aliphatic amino acid is 5-30 wt. % based on crucible solids in said washcoat slurry; the OSC material comprises a cerium-zirconium mixed oxide nanosol having an average particle size of less than 1 μm; The method of claim 4, wherein the inorganic oxide support is gamma-alumina having an average particle size of 2 to 8 μm.

20. The C in the washcoat slurry 2 ~C 6 the amount of aliphatic amino acid is 5-30 wt. % based on crucible solids in said washcoat slurry; said OSC material comprises a cerium-zirconium mixed oxide having an average particle size of 5-10 μm; 5. The method of claim 4, wherein the inorganic oxide support is nano alumina having an average particle size of less than 1 μm.

Citation Information

Patent Citations

  • Exhaust emission control method and exhaust emission control device

    JP2009299521A

  • Dispersion liquid, catalyst for exhaust purification and method for producing the same

    JP2017177014A

  • Method for coating a substrate with particulate stabilized foam - Patent Application 20070122997

    JP2019519354A

  • Post-treatment system of an exhaust gas, catalyst useful for said system and processes for their preparation

    WO2013046150A1